ISOTOPIC GEOCHRONOLOGY OF THE ARCHEAN POSTTECTONIC ASSOCIATION OF SANUKITOIDS, SYENITES, AND GRANITOIDS IN CENTRAL KARELIA - Bibikova E.V.; Petrova A.Yu.; Arestova N.A.; Levchenkov O.A.; Ivanikov V.V.; Claesson S. (My University, 2006)
The U-Pb geochronological study (by the classic technique and on an ion microprobe) of syenites from central Karelia has established their Archean age. The age values obtained for individual massifs are 2735 ± 15 Ma for syenites from the Sjargozero Massif and 2745 ± 10 Ma for syenite from the Khizhjarvi Massif. The syenites are demonstrated to have been emplaced nearly synchronously with sanukitoid massifs in central Karelia, whose average age is 2743 ± 3 Ma (Bibikova et al., 2005). The syenites of the Sjargozero Massif and granodiorites of the Ust-Volomsky Massif were determined to have practically identical ages of 2735 and 2738 Ma, respectively, a fact also corroborating the coeval character of the syenites and granodiorites. Some zircon grains from the Sjargozero syenites contain cores with an age of about 2755 Ma, which suggests that the syenites could have been contaminated with the material of the host volcanic rocks of basaltic and andesitic composition that were metamorphosed at 2750-2760 Ma. The results of the isotopic geochronologic research indicate that the different rock groups composing the Archean postorogenic association of sanukitoids, syenites, and granitoids in central Karelia have been generated in a single stage at approximately 2740 Ma, i.e., 60-70 m.y. after the origin of the syntectonic tonalites. The zircons have elevated Th/U ratios, which is consistent with the mantle genesis of the rocks. Significant crustal contamination was identified in the most acid members of the sanukitoid series: syenites and granitoids. Our data obtained for zircons from the sanukitoids and syenites of the Karelian craton in the Baltic Shield are in good agreement with the results obtained on the sanukitoids of the Canadian Shield. © Pleiades Publishing, Inc., 2006.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей